Probing the inner circumgalactic medium and quasar illumination around the reddest ‘extremely red quasar’ - Lau, Marie Wingyee; Hamann, Fred; Gillette, Jarred; Perrotta, Serena; Rupke, David S N; Wylezalek, Dominika; Zakamska, Nadia L (Monthly notices of the Royal Astronomical Society, 2022)
Dusty quasars might be in a young stage of galaxy evolution with prominent quasar feedback. A recently discovered population of luminous, extremely red quasars at z ∼ 2-4 has extreme spectral properties related to exceptionally powerful quasar-driven outflows. We present Keck/KCWI observations of the reddest known ERQ, at z = 2.3184, with extremely fast [O iii] λ5007 outflow at ∼6000 km s−1. The Lyα halo spans ∼100 kpc. The halo is kinematically quiet, with velocity dispersion ∼300 km s−1 and no broadening above the dark matter circular velocity down to the spatial resolution ∼6 kpc from the quasar. We detect spatially resolved He ii λ1640 and C iv λ1549 emissions with kinematics similar to the Lyα halo and a narrow component in the [O iii] λ5007. Quasar reddening acts as a coronagraph, allowing views of the innermost halo. A narrow Lyα spike in the quasar spectrum is inner halo emission, confirming the broad C iv λ1549 in the unresolved quasar is blueshifted by 2240 km s−1 relative to the halo frame. We propose the inner halo is dominated by moderate-speed outflow driven in the past and the outer halo dominated by inflow. The high central concentration of the halo and the symmetric morphology of the inner region are consistent with the ERQ being in earlier evolutionary stage than blue quasars. The He ii λ1640/Lyα ratio of the inner halo and the asymmetry level of the overall halo are dissimilar to Type II quasars, suggesting unique physical conditions for this ERQ that are beyond orientation differences from other quasar populations. We find no evidence of mechanical quasar feedback in the Lyα-emitting halo.